SOCIOECONOMIC DETERMINANTS OF HOUSEHOLD DEMAND FOR FOOD IN OSUN STATE NIGERIA - TOLORUNJU, ESTHER TOLUWATOPE; OSINOWO, OLATOKUNBO HAMMED; ADEKUNLE, CHIOMA PATRICIA; OLADEJI, SOLOMON OLADELE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
This study described the food demand of households in Osun State, Nigeria with a view to identifying the determinants of household food expenditure. Multistage sampling procedure was used to select 669 households in the study area and structured questionnaire was used to obtain primary data from respondents. Data on socio-economic characteristics and expenditure pattern were analysed using descriptive statistics while demand for food groups in this study was estimated using Quadratic Almost Ideal Demand System (QUAIDS) model. Findings revealed that 57.4% of the household heads were male, 56% were married, with a mean age and household size of 55 years and 7 persons respectively. Grains had the largest share of household total food expenditure, ranging from about 45% and 40 % among the high income quartiles and urban households to 63% and 52% among the low income quartiles and rural households. The poorest households had the least (N 7,817.35) mean food expenditure, with about 0.57% as food expenditure as percentage of income and the richest households had the highest (N 10,315.55) expenditure share. Result from the QUAIDS model revealed that budget share of households on grains/starch increases with increase in price of grains/starch (p<0.01), while it decreases with increase in prices of animal protein (p<0.01) and fat/oil (p<0.05). The study conclude that policy-makers should consider consumer behavior at different income levels, as this will affect the rate at which people have access to food as such enhancement programs needs to be region-specific especially in low income earning states and take into account these behavioral differences in food expenditures.